International New Ventures and Early Internationalization: Relational networks and workers specific skills as enhancing agents - Lobo, Carla Azevedo (2018)
Based on the opinions of different entrepreneurs, this study seeks to determine the importance of several factors as inducers of the internationalization process by companies that have internationalized early in their life cycle. Factors such as the relational networks, entrepreneurs’ specific skills and international experience of employees are considered. The empirical study was conducted on a sample of 320 Portuguese companies. Data Exploratory Analysis methodologies and Univariate Statistical Inference methodologies were used. Evidence was found for the importance of Relational Networks, for Specific skills of the employees, and for the International Experience of employees, in line with the chosen Theoretical Model.